Comparative study of religious cosmology in Sanskrit Bible and Vedic text - Balakailasanathasarma, M.; Navaneethakrishnan, S. (Department of Christianity University of Jaffna, 2018)
Nowadays majority of religious researches are focused on development of global humanity. Sri Lanka as a multi- religious, multi-lingual developing country should take appropriate measures for this process so that, where ever possible persons may have adequate opportunities to follow their religious believes. This research has a significant contribution to a sophisticated understanding of religious cosmological concepts in Christianity and Hinduism in relation. Current era compels to explore ways to build bridges between communities that are divided by their religious beliefs to respect each other. This study focused on interreligious aspects on cosmology in Vedic text and translation work of the Bible into Sanskrit by comparing the Vedic expositions regarding the creation of the Universe with Bible concepts. The Objective of this study is to identify some similarities in cosmic creation concept in Sanskrit bible and Vedic text with evidences. It is also try to define several remarkable aspects of Sanskrit bible terminologies as a source or target language in Bible translations. Mixed method including comparative and critical analytical methods is used to study both English and Sanskrit translations of bible. Findings of this study reveal that there are remarkable similarities observed in Pre-creation, Creation of heaven and the earth, Origin of Day and Night, Origin of the Water, Origin of plants and trees, Origin of sun and moon, Origin of living creatures, Order of evolution of cosmic elements. In a nutshell it could be concluded that various similarities could be observed in Sanskrit Bible translation and Vedic text and this study touched some of them for the better understanding.
Keywords: Christianity; Cosmology; Sanskrit Bible; Vedic tradition